Etika Jual Beli Kotoran Sapi dalam Pandangan Islam di Desa Pandanarum Kecamatan Tempeh Lumajang - Umi Suswati Risnaeni; Maisyarofah Maisyarofah (IQTISHODUNA: Jurnal Ekonomi Islam, 2017)
Islam is the only perfect religion that governs all human life and the universe including human economic activities are also regulated in Islam with the Divine principle. In the world of business, in Indonesia there is often a sale and purchase of dirt, while animal waste is basically a dirty object that is not desirable, but with the advancement of science and technology, it turns out that animal dung has many benefits. Based on the above facts, the author wants to examine and discuss and know the problem and then compiled it into a scientific work entitled: "ethics of buying cow dung in the Islamic view in the Village Pandanarum Kecamtan Tempeh". This research uses Descriptive Qualitative Method, with case study approach. Techniques of collecting data using interviews, observation and documentation. The data analysis using field descriptive analysis. The conclusion of the research is: 1) The results of the research that the author did in the ethics of buying and selling cow dung that is happening in the Village pandanarum, do not apply the ethics of buying cow dung karna in this case there are still people who sell sell cattle dung. 2) The sale and purchase of cow dung in the view of Islam is in accordance with Islamic Shari'ah because in this case the community has granted or menysugahkan cow dung 3) Ethical sale of cow dung in the view of Islam in the Village Pandanraum kecamtan Tempeh not apply the ethics of buying and selling cow dung because in this case masyarakt still do not know about the ethics in accordance with the teachings of Islam.